2017
DOI: 10.1111/1742-6723.12779
|View full text |Cite
|
Sign up to set email alerts
|

Hospital use in Aboriginal and non‐Aboriginal patients with chronic disease

Abstract: Aboriginal people use health services in a different manner when compared to non-Aboriginal people. In a subset of patients with chronic disease, high use may be reduced with better access to primary healthcare. Policy-makers and healthcare providers should examine healthcare use from primary to tertiary care among the Aboriginal population, with a particular focus on ED presentations; investigate the underlying causes driving specific patterns of health service utilisation among Aboriginal people; and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This is consistent with other research in the area of frequent admissions which reiterates the fact that a small proportion of patients account for a disproportionate share of avoidable admissions. [9,15] Research in the area of frequent avoidable admissions commonly aims to develop risk pro les or risk prediction tools to help identity those patients most at risk. [7,9,15] Our study showed that Aboriginal people experiencing avoidable admissions were more likely to be female, younger, single, have diabetes complications, asthma and COPD, live in moderately accessible to very remote locations, and to be more disadvantaged compared with non-Aboriginal people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with other research in the area of frequent admissions which reiterates the fact that a small proportion of patients account for a disproportionate share of avoidable admissions. [9,15] Research in the area of frequent avoidable admissions commonly aims to develop risk pro les or risk prediction tools to help identity those patients most at risk. [7,9,15] Our study showed that Aboriginal people experiencing avoidable admissions were more likely to be female, younger, single, have diabetes complications, asthma and COPD, live in moderately accessible to very remote locations, and to be more disadvantaged compared with non-Aboriginal people.…”
Section: Discussionmentioning
confidence: 99%
“…[9,15] Research in the area of frequent avoidable admissions commonly aims to develop risk pro les or risk prediction tools to help identity those patients most at risk. [7,9,15] Our study showed that Aboriginal people experiencing avoidable admissions were more likely to be female, younger, single, have diabetes complications, asthma and COPD, live in moderately accessible to very remote locations, and to be more disadvantaged compared with non-Aboriginal people. Further research in identifying a risk pro le for this vulnerable group of people would be helpful in creating appropriate community medical and prevention care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is comparable to other studies differentiating health care utilization in Indigenous and non-Indigenous Australians. Whyatt et al conducted a longitudinal cohort study from 2002 to 2014 comparing rates of hospital utilization in Indigenous and non-Indigenous Australians with chronic diseases [ 15 ]. Whyatt et al found that while inpatient length of stay in Indigenous Australian patients were similar to non-Indigenous patients (as we found in our study), Indigenous Australians had much higher rates of Emergency Department presentations, were more likely to be admitted as an inpatient, and were also younger than non-Indigenous Australians [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whyatt et al conducted a longitudinal cohort study from 2002 to 2014 comparing rates of hospital utilization in Indigenous and non-Indigenous Australians with chronic diseases [ 15 ]. Whyatt et al found that while inpatient length of stay in Indigenous Australian patients were similar to non-Indigenous patients (as we found in our study), Indigenous Australians had much higher rates of Emergency Department presentations, were more likely to be admitted as an inpatient, and were also younger than non-Indigenous Australians [ 15 ]. Common factors found in our study and other studies predicting increased healthcare utilization for Indigenous and non-Indigenous Australian patients include the presence of chronic disease and more telling, severity of disease.…”
Section: Discussionmentioning
confidence: 99%